Explicando a civilidade: contribuições das prioridades valorativas e do priming valorativo - Souza, Roosevelt Vilar lobo de (2015)
The priming of human values is studied insufficiently in the literature, defendant efforts that seek to prove their effectiveness in changing behavior. In this dissertation, adopting the functionalist theory of human values, we sought to contribute to the literature on this relationship. Thus were prepared four studies aiming to develop a reliable measure of civility, identify related evaluative this construct and evaluate the effect of priming values in this behavior. The first study aimed to develop a self-report scale of civility, and counted with the participation of 510 university students (M = 22.2, SD = 6.39; 56.2% female). Through an exploratory factor analysis (PAF method), this study showed a measure with three-factor structure, presenting satisfactory internal consistency indices (α > .80). The second study evaluated the evaluative correlates of civility, using the scale developed in Study 1, and tested the prediction of priming values in this construct and was used a sample of 184 university students (M = 24.7, SD = 7.03; 51.1% female). As a result, significant correlations were found between the sub-functions with type of central and personal guidance with the civility scale. However, the results showed no significant effect of priming values in this construct. The third study had the same objectives of the study two, however it was used as output variable an implicit measure of civility, seeking to reduce the bias inherent in the self-report measures. He was assisted with a sample of 65 university students (M = 20.5, SD = 2.49; 73.8% women). The results of this study showed significant results only for the correlation between the normative Sub and the implicit measure of civility. In addition, also met marginally significant relationship between supra Sub and measurement (p = 0.08). Concerning the influence of the priming on the implicit measurement values of civilization, there were no significant effects. The fourth and final study was the last attempt of this dissertation to confirm evaluative correlates of civility and evaluate the effect of different types of priming in this construct. To this end, counted with the participation of 61 university students (M = 22.5, SD = 4.72; 57.4% female). The results indicated significant correlations only between civility behavior and the supra Sub. In relation to priming values, again not yielded any significant results. Given the above, the results previously reported indicated that there is a clear relationship between the values and the civility behavior. However, the findings regarding the influence of priming values civility did not support the evidence that others present studies in the literature presented. These findings indicate that priming technique used was not effective to activate the evaluative content that could cause effects on behavior. Maybe by the relevant abstract character to construct stimulated, need more complex stimuli and involving greater effort, as the studies in the literature that found significant effects.